Epidermoid Carcinoma of the Cervix and Pregnancy. A case presentation. - Práxedes Rojas Quintana; Doris González Díaz; Carlos Pérez Velásquez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
A 25 year-old female patient with a 12 week pregnancy was presented. She was diagnosed with an ultered Pap test. She was referred to the cervix uterine pathology specialist where an exophytic lesion compatible to cervix uterine cancer in advanced stages. The treatment as well as the conduct followed by the specialist was really hard due to the patient´s pregnant condition.